Urgensitas Prenuptial Agreement Kalangan Pasangan Mahasiswa Ditinjau dari Status Hukum dan Kajian Gender: Studi Mahasiswa Magister Ilmu Syariah UIN Sunan Kalijaga Yogyakarta - Abdu Salafush Sholihin (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the urgency of prenuptial agreements among student couples from the perspective of positive law and gender studies. The research uses a normative-empirical juridical approach with data collection methods through interviews and literature studies. The results show that prenuptial agreements have an important role in providing legal protection for the rights and obligations of married couples, especially in regulating the division of assets, dealing with issues of infidelity, domestic violence, and preventing polygamy. From a gender perspective, this agreement is also seen as an effort to reduce gender inequality by allowing women to continue their education and career without being distracted by domestic burdens. The interview results show two different views: the first informant supports prenuptial agreements as a preventive measure to protect rights in marriage, while the second informant prefers oral commitments that rely on trust and open communication. This study concludes that the urgency of making a prenuptial agreement largely depends on the needs of the individuals and the social context of the couple, although there are still challenges in the legalization process and society's understanding of prenuptial agreements.